A near-real-time ficin-based inhibitive enzyme assay for biomonitoring heavy metals in waters near Kuah’s Jetty, Langkawi - Uba, Garba; Manogaran, Motharasan; Halmi, Mohd Izuan Effendi; Sabullah, Mohd Khalizan; Ayuningrum, Diah; Shukor, Mohd Yunus (Hibiscus Publisher Enterprise, 2024)
Near real-time biomonitoring, particularly through enzyme assays, offers exceptional sensitivity to bioavailable pollutants, delivering rapid results that facilitate timely intervention. This method is crucial for reducing pollution in drinking water systems and safeguarding human and animal health. The marriage of biological and instrumental process of monitoring allows only positive samples be sent for instrumental analysis vastly increasing the frequency of monitoring and reducing cost at the same time. This study demonstrates the application of ficin as an inhibitive enzyme assay for biomonitoring, in a near real time setting, specifically targeting heavy metals in environmental samples from waters near Kuah’s Jetty, Langkawi. Using the ficin dye-binding assay, designed to detect mercury silver (Ag+), (Hg2+), and copper (Cu2+) at sub-ppm levels, we validated its ability to identify trace concentrations of these metals in waters. The assay proved to be sensitive, rapid, and cost-effective, with minimal inhibition (<10%) during a 6-hour field trial, indicating low pollution levels, which was further corroborated through instrumental analysis. This method enables the swift identification of pollutants, prompting timely action and supporting the preservation of ecotourism sites by providing empirical data for policy development. The simplicity and visual appeal of enzyme assays make them excellent tools for education, fostering environmental awareness and conservation efforts. Our findings underscore the potential of enzyme assays for large-scale environmental monitoring, aligning local practices with international standards and promoting global cooperation in environmental conservation. This study enhances our understanding of ecological health in marine and brackish ecosystems, emphasizing the need for continuous monitoring to protect natural habitats.